Access to Hematopoietic Stem Cell Transplantation in Brazil: facing our challenges. : Hematopoietic Stem Cell Transplantation (HSCT) for all session SBTMO 2023 - Funke, Vaneuza Araujo Moreira; Bonfim, Carmen; Darrigo Juniro, Luiz Guilherme; Barroso Duarte, Fernando (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
At the Session HSCT for all in SBTMO 2023 the main current challenges for the transplant in Brazil were discussed with panelists an the cordinator of National Transplant System. This article has the objective of reporting the main aspects of the discussion for future actions. Access to beds for adult and pediatric patients, better distribution througout the country, acces to critical medications such as antiviral drugs and imunnessupressors for GVHD phrophylaxis and therapy were discussed. The need for data managers at the centers fostering the transplant data registry was also pointed out. Extension of this discussion among transplant centers and goverment is very important in order to find solutions for improvement in HSCT in Brazil.